Acceptability of an asymptomatic COVID-19 screening program for schools in Victoria, Australia: a qualitative study with caregivers from priority populations - Isabella Overmars; Frances Justice; Jessica Kaufman; Jane Tuckerman; Margie Danchin (Sax Institute, 2024)
Background: An asymptomatic COVID-19 rapid antigen testing (RAT) screening program was implemented in Victorian schools in January 2022, to support keeping schools open throughout the pandemic. This study explored compliance with the program among caregivers from priority populations in Victorian mainstream and specialist schools. Methods: We conducted semi-structured interviews between 7-31 March 2022 with caregivers of school-aged children participating in the RAT program in Victoria. Participants were asked about awareness, acceptability, compliance, frequency, and barriers to testing. Recordings were transcribed and deductively analysed using a framework approach. Results: Fifty caregivers participated. They expressed confusion about the 'recommended' program, assuming it was mandatory. Caregivers wanted notification from schools of positive cases to increase motivation for compliance. Culturally and linguistically diverse (CALD) families were compliant; however, in-language resources were limited. Aboriginal or Torres Strait Islander (Koori) families tested less regularly and received information from their community rather than school. Caregivers of children living with disabilities reported behavioural challenges to testing, resulting in distress or non-compliance, and received non-specific information for their children. Conclusions: To increase engagement with future surveillance programs, caregivers need clarity about optionality, conducting tests, reporting results, and timely notification of cases. Requirements unique to each priority population include: accurate in-language information for CALD caregivers, community-led communication for Koori caregivers, tailored information, less testing, and flexibility for caregivers of children living with a disability. Keeping schools open and having tailored strategies to ensure equitable access for priority populations are essential for future pandemic management.